POTENSI BAKTERI RHIZOSPER PISANG SEBAGAI AGEN ANTAGONIS LAYU FUSARIUM PISANG (Fusarium oxysporum f.sp. cubense) SECARA IN VITRO - Saylendra, Andree; Rusbana, Tubagus Bahtiar; Maulana, Arif (Jurnal Agroekoteknologi, 2015)
The research was conducted to explore and determine the presence of antagonistic bacteria on banana plants (Musa spp) to inhibit (Fusarium oxysporum f.sp. cubense). The research was conducted in the laboratory of Agroekoteknologi, Faculty of Agriculture, Sultan Ageng Tirtayasa University. The experiment was arranged in non-factorial Randomized Completely Design (RCD) using 3 replication. The treatment consisted of 9 rhizobacteria isolates acquired from rhizosper of roots of banana on first screening. The test results showed antagonistic in vitro testing is able to inhibit the mycelium growth of Foc where the greatest inhibition was shown by BR 45 and BR 15 with the largest percentage inhibition of 88.90% and 87.78%. Observations on colony morphology showed 7 rhizosphere bacterial, genus observed as Bacillus sp. and that besides it was not identified. Research showed that the bacteria could potentially control the banana root disease caused by Fusarium.